If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b(b + 7) + -7(b + 7) = 0 Reorder the terms: b(7 + b) + -7(b + 7) = 0 (7 * b + b * b) + -7(b + 7) = 0 (7b + b2) + -7(b + 7) = 0 Reorder the terms: 7b + b2 + -7(7 + b) = 0 7b + b2 + (7 * -7 + b * -7) = 0 7b + b2 + (-49 + -7b) = 0 Reorder the terms: -49 + 7b + -7b + b2 = 0 Combine like terms: 7b + -7b = 0 -49 + 0 + b2 = 0 -49 + b2 = 0 Solving -49 + b2 = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '49' to each side of the equation. -49 + 49 + b2 = 0 + 49 Combine like terms: -49 + 49 = 0 0 + b2 = 0 + 49 b2 = 0 + 49 Combine like terms: 0 + 49 = 49 b2 = 49 Simplifying b2 = 49 Take the square root of each side: b = {-7, 7}
| r(r+4)-4(r+4)= | | p(p-2)+4(p-2)= | | x-4540=40 | | Y=150+0.7(Y-200)+50+0.2Y+200 | | x(x+2)+3(x+2)= | | -7(x-3)=63 | | 342+x=442 | | 8(2+z)-5(3-2z)= | | 2-3x=5x-2(x+8) | | 3(4-5a)-2(5-4a)= | | x-240=10 | | 4(y-6)-5(3y-1)= | | 7-2(x-4.5)=6-4x | | 6(3a+5)-3(2a-5)= | | 14+x=25 | | 2x+4y-7=0 | | 11(t+1)+2(t+5)= | | 2(a+1)+3(a+2)= | | a^2-a^2=a^4-1 | | 10x=570 | | 3y-20=7 | | 2x+4x+4x=50 | | 2(5)-10= | | 2(3)-10= | | 11x^2-34x+3=0 | | 11x^2-34x+13=0 | | 3/(3x)-1/(x+1)=1 | | 4w=w-(w-8) | | 1785y+140p-679y= | | 1/4x-32 | | 17+4x=33 | | 4(x-8)=-2 |